University as a driver for economic and social development of a region (on the example of the Republic of Kalmykia) - G. V. Ulanova (Новые технологии, 2018)
The article considers the role of regional universities in socio-economic development of the regions on the example of the Kalmyk State University named after. B.B. Gorodovikov. The author concludes that today KalmSU plays an essential role in the economic and social development of the Republic of Kalmykia and in the creation of an innovation-oriented economy, in providing the region with highly qualified personnel.